2018
DOI: 10.4314/ovj.v8i2.16
|View full text |Cite
|
Sign up to set email alerts
|

First report of camel contagious ecthyma in Nigeria

Abstract: Camel contagious ecthyma (CCE) is a viral disease of camelids that is caused by a Parapoxvirus (PPV) which is a DNA virus of the viral family: Poxviridae. Diseases affecting camels in Nigeria are scarcely reported. CCE or the laboratory detection of camel PPV (CPPV) has not been reported in Nigeria. This study investigated and described the clinical presentation of CCE and molecular detection of CPPV in Nigeria. Suspected cases of CCE were reported in a farm, live animal market and abattoir, in three different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Thus, reliable estimate of the true prevalence of the disease in the country is currently lacking. In recent times, different techniques such as physical examination for clinical signs and PCR have been used to confirm contagious ecthyma outbreaks in Nigeria [ 1 , 2 , 4 ]. Furthermore, previous study conducted in 2018 involving three flocks of goats in northern Nigeria reported a mortality rate of 100% [ 4 ] in two out of the three flocks investigated, which was higher than usually observed in CE outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, reliable estimate of the true prevalence of the disease in the country is currently lacking. In recent times, different techniques such as physical examination for clinical signs and PCR have been used to confirm contagious ecthyma outbreaks in Nigeria [ 1 , 2 , 4 ]. Furthermore, previous study conducted in 2018 involving three flocks of goats in northern Nigeria reported a mortality rate of 100% [ 4 ] in two out of the three flocks investigated, which was higher than usually observed in CE outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Contagious ecthyma (CE) is a highly contagious viral disease of small ruminants such as sheep and goats [1] that occasionally affects camels [2] and wild ruminants with huge economic impact on the livestock industry [2][3][4][5][6]. Clinically, the disease is associated with skin lesions such as erythema, macules, papules, vesicles, pustules and crusts on the lips, tongue, teat, nose, hooves and other parts of the body [6] especially in young lambs and kids [3,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies have been published on camelpox in Kenya since 1997 [40]. Contagious ecthyma, caused by a parapox virus [103,104], was reported in camels in two medium quality studies. One reported on an outbreak of clinical disease in Laikipia in 1984 [47], while the other presented results of a cross-sectional survey in Turkana (Table 4) [46].…”
Section: Virusesmentioning
confidence: 99%
“…Orf is usually transmitted to humans through direct contact with infected sheep, goats, or reindeer. Although there are multiple reports of camels infected with orf, 2,3 there is no reported case of transmission to humans. Camel contagious ecthyma (CCE), a highly infectious viral disease of camels caused by a PPV, has been reported in many countries, such as Saudi Arabia, Bahrain, Iran, Sudan, and Nigeria.…”
mentioning
confidence: 99%